Distribución espacial del grado de pendiente del terreno y su relación con la producción y rentabilidad de campos comerciales de maíz, en la zona de Ventanas. - Rosado De La Vera, Kimberly Virginia (2021)
The slope of the land plays an important role in the level of erosion and therefore in the yield of crops, so it is important to quantify its effect on different parameters of the same. For this reason, the objective of this research was to determine the structure and distribution of the degree of slope in the land, and its relationship with the production, profitability and technical management of soil management in commercial corn crops. For the field work, 20 corn farms located in the Ventanas canton, in the Los Ríos province, were selected. The evaluated treatments were: P1: Flat (0 - 2.0 %), P2: Slight incline (2.1 - 5.0 %), P3: Little incline (5.1 - 10.0 %), P4: Moderate incline (10.1 - 15.0 %), P5: Moderate-high incline (15.1 - 20.0 %), P6: High incline (20.1 - 25.0 %) and P7: Very high incline (25.1 - 30.0 %). A Completely Random Design (DCA) was used with seven treatments in two repetitions. The results obtained allowed to identify that the structure of the distribution of the slope that predominates is that of little inclination (5.1 to 10.0 %), corresponding to 27.78 % of the evaluated area, followed by the slight inclination (2.1 - 5.0 %) that covered the 22.82 % of the area studied between the four areas of the canton Ventanas. In the areas where the correlation coefficients were significant, a negative linear effect of the increase in the slope could be observed on the variables ear length, diameter, weight of 1000 grains, as well as on yield. Both the performance and the economic profitability are directly conditioned by the progressive increase of the slope, being less as the slope of the terrain increases, restricting performance, and increasing labor costs. The Emblema hybrid registered the highest level of performance in the four zones regardless of the slope of the terrain, with an average of 8860.71 kg ha-1; while the other hybrids reached yields that fluctuated between 6787.00 kg ha-1 and 8467.79 kg ha-1. The lack of soil analysis, added to the burning of corn crop stubble, give indications of wrong soil management, which undermines the sustainability of the corn production units. Keywords: Slope, technical management, profitability, erosion, structur